Modelling the spatial abundance of a migratory predator: A call for transboundary marine protected areas. Issue 3 (9th January 2019) - García‐Barón, Isabel; Authier, Matthieu; Caballero, Ainhoa; Vázquez, José A.; Santos, M. Begoña; Murcia, José Luis; Louzao, Maite
Abstract: Aim: During their migration, highly mobile species cross multiple jurisdictional boundaries and multiple not‐specific marine protected areas (MPAs). When identifying the critical habitats where individuals aggregate, these areas can be ideal candidates for MPAs. This study was focused on the endangered fin whale ( Balaenoptera physalus ) for which there is little knowledge on its distribution and abundance in non‐breeding temperate latitudes. Location: Bay of Biscay (BoB). Methods: Firstly, we modelled the relative abundance of fin whales by means of generalized additive models (GAMs) using data collected on the PELACUS (2007–2008) and JUVENA (2013–2016) oceanographic surveys during late summer. Secondly, we evaluated the reliability of the predictions by distinguishing environmental extrapolations and interpolations. Finally, we identified critical areas of highest predicted abundance and we assessed whether existing MPAs comprised within the Natura 2000 network and designated for other species offer protection to fin whales in the BoB. Results: Fin whales were especially abundant in deep off‐shore waters, mainly associated with intermediate temperature water values in the inner part of the BoB. The years with the highest relative predicted abundances (an average of 1, 500 whales) matched with years when warmer sea surface temperature extended into larger areas. In colder years, the average predicted abundance dropped to 400 whales. The main critical area for fin whales (defined by the highest 40% of abundance) was common for both surveys, and it was located in the south‐eastern part of the BoB. Main conclusions: Our study contributes to the identification of important concentration areas of fin whales during late summer, based on reliable spatial predictions. The assessment of the current Natura 2000 network highlights the fact that only three MPAs marginally covered the critical area we have identified for fin whales. We propose a transboundary potential MPA to aid the conservation of the species in the BoB.